A critical race study of non-statutory mental healthcare for young people racialised as black - Salla, Anthony (2020)
This was a study of the experiences of young Black people, their pathway to, and experience of, non-statutory mental healthcare. Non-statutory support is that offered by voluntary and community-sector organisations, including churches, community-interest companies and small-scale private providers.